2012
DOI: 10.1016/j.ejphar.2012.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory milieu as an early marker of kidney injury in offspring rats from diabetic mothers

Abstract: The present study investigated the early presence of inflammatory response in renal tissue of young offspring from diabetic mothers. The effect of L-arginine (L-arg) supplementation was also investigated. The offspring was divided into four groups: group CO (controls); group DO (diabetic offspring); group CA (CO receiving 2% L-arg solution) and group DA (DO receiving the 2% L-arg solution). Glycemia, arterial pressure and renal function were evaluated; gene and protein expression of pro-inflammatory cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(50 reference statements)
0
6
1
Order By: Relevance
“…They demonstrated that the expression of inflammatory cytokines could be triggered early in the life of the offspring, at the moment when renal injury had not been detected by clinical parameters (19). A study, that used a similar methodology that we used, described the increase in cytokines in the offspring at 2 mo from diabetic dams induced by streptozotocin (20). However, our data did not demonstrate changes in markers of EMT in the absence of lesions in animals with 2 mo.…”
Section: Discussioncontrasting
confidence: 49%
“…They demonstrated that the expression of inflammatory cytokines could be triggered early in the life of the offspring, at the moment when renal injury had not been detected by clinical parameters (19). A study, that used a similar methodology that we used, described the increase in cytokines in the offspring at 2 mo from diabetic dams induced by streptozotocin (20). However, our data did not demonstrate changes in markers of EMT in the absence of lesions in animals with 2 mo.…”
Section: Discussioncontrasting
confidence: 49%
“…Increased basal BP has been shown in childhood and adolescence of preeclamptic or hypertensive mothers, 27 or in the offspring of rat dams with diabetes, 19 protein restriction, 11 and uteroplacental insufficiency 16 during pregnancy. Alterations of the RAAS and proinflammatory cytokines in peripheral tissues and plasma have been implicated as important mediators in the fetal programming of increased BP.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, Mizuno and colleagues demonstrated that the RAAS contributes to the enhancement of the renal sympathetic and pressor responses to physical stress in male offspring exposed to maternal protein restriction. 17,18 Recent studies also indicate that activation of inflammatory pathways is present early in the kidney of offspring from diabetic dams, 19 and that early life NF-κB dyshomeostasis in conduit arteries induced by prenatal inflammatory exposure plays a role in the development of hypertension through triggering RAAS overactivity. 20 Most of these previous studies have focused on the roles of the peripheral RAAS and SNA in the development of hypertension in prenatally programmed hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study on the offspring of diabetic rats correlated the expression of this proinflammatory cytokine with the chronic activation of the innate immune system in response to the increased insulin resistance [16]. Moreover, because of fetal programming, it is believed that the dysfunction of fetal pancreatic β cells caused by gestational DM results in permanent metabolic disturbance in postnatal and adult life [16, 17], severe insulin resistance [5, 16], a reduction in the number of nephrons and glomeruli, and impaired glomerular filtration rate [5]. Therefore, these data may explain the higher expression of MCP-1 in DC5 cases compared to the CC5 cases.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine may mediate acute forms of renal injury, as well as being involved in the development of chronic kidney disease [18]. Thus, it can be inferred that the injuries caused by folic acid [15] and by fetal reprogramming [16] increase the expression of IL-1 in the two-month-old offspring.…”
Section: Discussionmentioning
confidence: 99%